Inducible, reversible system for the rapid and complete degradation of proteins in mammalian cells - Holland, Andrew J; Fachinetti, Daniele; Han, Joo Seok; Cleveland, Don W (Proceedings of the National Academy of Sciences - PNAS, 2012)
Inducible degradation is a powerful approach for identifying the function of a specific protein or protein complex. Recently, a plant auxin-inducible degron (AID) system has been shown to degrade AID-tagged target proteins in nonplant cells. Here, we demonstrate that an AID-tagged protein can functionally replace an endogenous protein depleted by RNAi, leading to an inducible null phenotype rapidly after auxin addition. The AID system is shown to be capable of controlling the stability of AID-tagged proteins that are in either nuclear or cytoplasmic compartments and even when incorporated into protein complexes. Induced degradation occurs rapidly after addition of auxin with protein half-life reduced to as little as 9 min and proceeding to completion with first-order kinetics. AID-mediated instability is demonstrated to be rapidly reversible. Induced degradation is shown to initiate and continue in all cell cycle phases, including mitosis, making this system especially useful for identifying the function(s) of proteins of interest during specific points in the mammalian cell cycle.